Tailoring combinatorial lipid nanoparticles for intracellular delivery of nucleic acids, proteins, and drugs - Yamin Li; Zhongfeng Ye; Hanyi Yang; Qiaobing Xu (Elsevier, 2022)
Lipid nanoparticle (LNP)-based drug delivery systems have become the most clinically advanced non-viral delivery technology. LNPs can encapsulate and deliver a wide variety of bioactive agents, including the small molecule drugs, proteins and peptides, and nucleic acids. However, as the physicochemical properties of small- and macromolecular cargos can vary drastically, every LNP carrier system needs to be carefully tailored in order to deliver the cargo molecules in a safe and efficient manner. Our group applied the combinatorial library synthesis approach and in vitro and in vivo screening strategy for the development of LNP delivery systems for drug delivery. In this Review, we highlight our recent progress in the design, synthesis, characterization, evaluation, and optimization of combinatorial LNPs with novel structures and properties for the delivery of small- and macromolecular therapeutics both in vitro and in vivo. These delivery systems have enormous potentials for cancer therapy, antimicrobial applications, gene silencing, genome editing, and more. We also discuss the key challenges to the mechanistic study and clinical translation of new LNP-enabled therapeutics.